The Effect of Characteristics of Audit and Board of Directors on Real Earnings Management in Companies Listed on the Indonesia Stock Exchange - Agustin, Greece; Karina, Ria (ACCOUNTABILITY, 2021)
This study aims to examine the effect of the characteristics of the audit and board of directors on real earnings management. In terms of limiting real earnings management by a company manager, there are characteristics of audit. Characteristics of the audit are the most important part in the structure of a company and government. An audit that works efficiently and well will generate positive corporate profits. This study uses data from all companies listed on the Indonesia Stock Exchange (IDX) which include annual reports from 2016 to 2020. Sampling of data was done by purposive sampling technique. This study combined the research object and one time dimension. This research was conducted using panel data regression test based on data that had been collected using SPSS and Eviews 10 software. The best model chosen for this research model was the Fixed Effect Model. The results showed that the characteristics of the audit and board of directors has no influence on the dependent variable real earnings management which could be seen from the probability value of the T test results. Meanwhile, the independent director has a significant positive on real earnings management.